Development of Al-Qur'an Memorization Techniques Based on Computer File Models: Learning Innovation in Islamic Education - Khoirotul Idawati; Hanifudin Hanifudin (Pascasarjana Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2024)
This study aims to develop an innovative Qur'an memorization technique by utilizing a computer file model in the context of Islamic education. The method used is Research and Development (RnD), which includes needs analysis, design, development, and evaluation of learning products. The results of the study indicate that this technique is effective in improving students' understanding and memorization abilities, thanks to the integration of creative elements such as imagination, visualization, association, and the use of color and music. Students involved in this technology-based learning reported increased motivation and interest in memorizing the Qur'an. This finding implies that the use of technology in the teaching and learning process can enrich traditional methods, making them more relevant to the development of the times and the needs of the younger generation. This method is expected to be adopted more widely in Qur'an education to encourage the effectiveness and efficiency of memorization